HUBUNGAN EKSPOR, IMPOR, INFLASI, DAN JUMLAH UANG BEREDAR TERHADAP PERTUMBUHAN EKONOMI INDONESIA DENGAN NILAI TUKAR SEBAGAI MEDIASI - Budiman, Johny; Arifin, Supriyadi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The economic level of a country can be identified by looking at its economic growth. Economic growth in each period will not be consistent all the time, but will experience periodic fluctuations.The aim of this research is to examine the connection between exports, imports, inflation, the amount of money in circulation and economic growth through the exchange rate in Indonesia. This research uses multiple linear regression analysis methods with secondary data. The data used consists of information regarding exports, imports, inflation, money supply, exchange rates and Indonesia's economic growth. In terms of data collection time, this type of data study uses time series data collected from the years 2018-2022 with SPSS 21. Based on the results of research that has been carried out, direct influence shows that exports & imports do not have a significant effect on economic growth, while inflation & money supply has a significant positive effect on economic growth. Apart from that, the indirect effect shows that exports through the exchange rate have a positive and insignificant effect on economic growth, money supply through the exchange rate has a positive and significant effect on economic growth, while imports & inflation through the exchange rate have no significant effect on economic growth.